Initial Motivations for Choosing Teaching as a Career - Alvariñas-Villaverde, Myriam; Domínguez-Alonso, José; Pumares-Lavandeira, Lucía; Portela-Pino, Iago (Frontiers in Psychology, 2022)
The objective of the study is to verify the reliability and validity of the Factors Influencing Teaching Choice, as well as to determine the teaching of Early childhood and Primary education students’ motivations and perceptions for the choice of this degree. The sample consisted of 262 student teachers aged between 18 and 27 (83.2% female and 16.8% male). According to degree, 54.2% of the participants were enrolled in Early Childhood Education and 45.8% in Primary Education. The instrument used in the study was the Factors Influencing Teaching Choice, FIT-Choice Scale, adapted to Spanish by Gratacós and López-Jurado. Results evidenced the high reliability and validity of the scale that is similar to the original model, presenting 12 motivational factors and 6 perceptions. The main reasons that lead to choose teaching profession, despite gender differences, are: having influence in the educational children’s process, the intrinsic value of the qualification, the fact that this profession contributes socially, or working with children. Also, students consider that teaching is a demanding profession and they are satisfied with the degree choice. The most important factors influencing the choice of education degree are intrinsic motivations and perceptions as the vocation, in contrast to external reasons such as economic incentives or social recognition.